Short Communication: Isolation and biochemical characterization of Rhizobium strains from nodules of lentil and pea in Tarai agro-ecosystem, Pantnagar, India - SANDEEP PRAKASH UPADHAYAY; NAVNEET PAREEK; GAURAV MISHRA (Smujo International, 2015)
Abstract. Upadhayay SP, Pareek N, Mishra G. 2015. Isolation and biochemical characterization of Rhizobium strains from nodules of lentil and pea in Tarai agro-ecosystem, Pantnagar, India. Nusantara Bioscience 7: 73-76. Root nodules were collected from young and healthy seedling of Pisum sativum L and Lens culinaris L from the field at different locations of Norman E. Borloug Crop Research Center, G.B.P.U.A. & T., Pantnagar, Uttarakhand state, India. Fifteen Rhizobium strains were isolated from the root nodule of P. sativum and L. culinaris and characterized by standard tests. All strains were gram-negative and did not absorb red color when cultured in YEMA containing congo red. In the ketolactose test yellowish zone of Cu2O not found. Also, isolates showed either poor or no growth on the glucose peptone medium after one day which is indicating character of rhizobia Thirteen isolates were fast grower and only two were slow growers which is confirmed by bromothymol blue test. Results confirmed that isolated strains were Rhizobium.